Clinical guidelines for caring for women with COVID-19 during pregnancy, childbirth and the immediate postpartum period. Issue 5 (September 2021) - Pavlidis, Pollyanna; Eddy, Katherine; Phung, Laura; Farrington, Elise; Connolly, Mairead; Lopes, Rudy; Wilson, Alyce N.; Homer, Caroline S.E.; Vogel, Joshua P.
Abstract: Background: The spread of the novel coronavirus (COVID-19) was declared a pandemic by the World Health Organization on 11th March 2020. Since then there has been a rapid rise in development of maternal and perinatal health guidelines related to COVID-19. The aim of this project was to develop a database of Australian and international recommendations relating to antenatal, intrapartum and postpartum care of women during the COVID-19 pandemic, in order to identify inconsistencies in clinical guidance. Methods: We conducted weekly web searches from 30th March to 15th May 2020 to identify recommendations pertaining to the care of women during pregnancy, labour and postpartum period from national or international professional societies, specialist colleges, Ministries of Health, Australian state and territory governments, and international guideline development organisations. Individual recommendations were extracted and classified according to intervention type, time period, and patient population. Findings were reported using descriptive analysis, with areas of consensus and non-consensus identified. Results: We identified 81 guidelines from 48 different organisations. Generally, there was high consensus across guidelines for specific interventions. However, variable guidance was identified on the use of nitrous oxide during labour, administration of antenatal corticosteroids, neonatal isolation after birth, labour and birth companions, and the use of disease modifying agents for treating COVID-19. Conclusion: Discrepancies between different guideline development organisations creates challenges for maternity care clinicians during the COVID-19 pandemic. Collating recommendations and keeping up-to-date with the latest guidance can help clinicians provide the best possible care to pregnant women and their babies.